A study of the English teaching practice at a language institute - Posada Ortiz, Julia Zoraida; Patiño Garzón, Luceli (Colombian Applied Linguistics Journal, 2007)
This study aims to describe the pedagogical practices that take place at the Language Institute of a university based on the observation of classes, questionnaires and interviews of teachers and students. In order to achieve the purpose of the project, the researchers adopted a qualitative approach and also combined an ethnographic perspective which denotes a constant reflection on the part of the teachers who participated as objects of the study. The results of the study demonstrate that most of the teachers employ the PPP (Presentation, Practice, and Production) model to language teaching and that the students make use of direct and indirect strategies in order to help themselves learning.